Minat masyarakat terhadap produk-produk asuransi syariah di Kota Malang - Sabila, Maulia Rosma (Maliki Interdisciplinary Journal, 2024)
Future risk limitation can be overcome by the use of insurance, especially sharia insurance. The purpose of sharia insurance is to make preparations in the face of possible difficulties faced by humans in the future. However, in reality, public interest in Islamic insurance products is still very small. This is influenced by the decision-making factors of customers in using Islamic insurance, which is very important to pay attention to for the sustainability and existence of the institution. This research is included in the type of qualitative research using a process in the form of literature review data collection. Islamic insurance in Indonesia is included in the DSN-MUI fatwa. The principles of sharia insurance or Islamic insurance are in accordance with the legal basis, namely the Koran and Hadith. The use of Islamic insurance also uses a clear contract that does not contain gharar, maysir (gambling), usury, zhulm (persecution), risywah or bribery, prohibited goods, and sin so that the parties to the contract are mutually responsible between customers and Islamic insurance companies. This aims to increase public interest in Islamic insurance products.